Odontología y trastornos respiratorios: apnea del sueño - Mira-L., Nadia Riguey (Revista Facultad de Odontología Universidad de Antioquia, 2009)
Sleep – disordered breathing is becoming of interest for health professionals because it’s an important problem in children, adolescents and adults, leading to significant consequences in health as well as psychomotor and social ones. Obstructive sleep apnea, specifically described as main element of obstructive sleep apnea syndrome, is the most common symptom of these sleep disorders according to published studies in medical and dental journals. Dentistry has begun to play a primordial role in syndrome diagnosis and treatment, so it could be an important expansion opportunity of our clinical practice. This article gathers the fundamental concepts which have been described by researchers dedicated to study the obstructive sleep apnea, in order to give to the readers the basic information for the problem recognition.